WARMER URBAN CLIMATES FOR DEVELOPMENT OF GREEN SPACES IN NORTHERN SIBERIAN CITIES - Igor Esau; Victoria Miles (Russian Geographical Society, 2016)
Modern human societies have accumulated considerable power to modify their environment and the earth’s system climate as the whole. The most significant environmental changes are found in the urbanized areas. This study considers coherent changes in vegetation productivity and land surface temperature (LST) around four northern West Siberian cities, namely, Tazovsky, Nadym, Noyabrsk and Megion. These cities are located in tundra, forest-tundra, northern taiga and middle taiga bioclimatic zones correspondingly. Our analysis of 15 years (2000–2014) Moderate Resolution Imaging Spectroradiometer (MODIS) data revealed significantly (1.3 °C to 5.2 °C) warmer seasonally averaged LST within the urbanized territories than those of the surrounding landscapes. The magnitude of the urban LST anomaly corresponds to climates found 300–600 km to the South. In the climate change perspective, this magnitude corresponds to the expected regional warming by the middle or the end of the 21st century. Warmer urban climates, and specifically warmer upper soil layers, can support re-vegetation of the disturbed urban landscapes with more productive trees and tall shrubs. This afforestation is welcome by the migrant city population as it is more consistent with their traditional ecological knowledge. Survival of atypical, southern plant species encourages a number of initiatives and investment to introduce even broader spectrum of temperate blossoming trees and shrubs in urban landscapes. The unintended changes of the urban micro-climates in combination with knowledgeable urban planning could transform the Siberian pioneer settlements into places of belonging.